2010
DOI: 10.1177/0271121410378759
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Challenging Behavior of Young Children Through Systematic Function-Based Intervention

Abstract: A decision model was used to systematically construct function-based interventions for the disruptive behaviors of three young children (ages 3.75-4.75 years) receiving special education services in inclusive preschool settings. The study was conducted in three phases. In Part 1, descriptive functional behavioral assessments (FBAs) were conducted. Each FBA included structured interviews and direct observations that were used to identify the functions of target behaviors. In Part 2, function-based interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…In general, findings are in accordance with previous research showing function-based interventions decreasing challenging behavior and increasing task engagement of preschool children (Blair et al, 2007(Blair et al, , 2010Wood et al, 2011), elementary students (Lane et al, 1999;O'Neill & Stephenson, 2009;Reid & Nelson, 2002), and secondary students (Majeika et al, 2011;Whitford et al, 2013). Large effect sizes were observed for all variables at different school levels, with the exception medium effects on disruptive behavior of students in secondary school.…”
Section: Changes In Pupils' Behavior and Task Engagementsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, findings are in accordance with previous research showing function-based interventions decreasing challenging behavior and increasing task engagement of preschool children (Blair et al, 2007(Blair et al, , 2010Wood et al, 2011), elementary students (Lane et al, 1999;O'Neill & Stephenson, 2009;Reid & Nelson, 2002), and secondary students (Majeika et al, 2011;Whitford et al, 2013). Large effect sizes were observed for all variables at different school levels, with the exception medium effects on disruptive behavior of students in secondary school.…”
Section: Changes In Pupils' Behavior and Task Engagementsupporting
confidence: 91%
“…Research has shown function-based interventions to be more effective than interventions that do not take into account maintaining consequences of problem behavior (Bellone, Dufrene, Tingstrom, Olmi, & Barry, 2014;March & Horner, 2002). Also, function-based interventions have been found to effectively decrease behavior problems and/or increase task engagement of students in general education environments at different school levels: preschool (Blair, Fox, & Lentini, 2010;Blair, Umbreit, Dunlap, & Jung, 2007;Wood, Ferro, Umbreit, & Liaupsin, 2011), elementary school (Gage et al, 2012;Lane, Umbreit, & Beebe-Frankenberger, 1999;O'Neill & Stephenson, 2009;Petursdottir, 2011;Reid & Nelson, 2002), and high school (Lane, Kalberg, & Shepcaro, 2009;Majeika et al, 2011;Whitford, Liaupsin, Umbreit, & Ferro, 2013). Thus, function-based interventions can reduce the need for segregated placements and serve as useful tools for inclusion (Benazzi, Horner, & Good, 2006).…”
Section: Function-based Interventionsmentioning
confidence: 99%
“…Natural Environment: The natural environment encompasses all living and non-living things naturally occurring on Earth, including water, air, mineral, climate, natural disasters, previously living organisms, forests, fields, lakes, mountains, and undeveloped natural vegetation that humans interact with on a daily basis [9,55] . Studies have shown that activity in the natural environment can promote health and well-being by improving mental and social health, longevity, ecological knowledge, activity, and feelings of community safety [17,25,[55][56][57][58][59] . Studies examining biological responses (e.g., blood pressure, heart rate and cortisol levels) have also shown that interactions with the natural environment reduce stress levels and improve overall well-being [55,57,58] .…”
Section: Components Of the Frameworkmentioning
confidence: 99%
“…Numerous studies have been conducted on the use of IPBS with young children (e.g., Blair, Umbreit, & Eck, 2000 ;Duda, Dunlap, Fox, Lentini, & Clarke, 2004 ;Gettinger & Stoiber, 2006 ;McLaren & Nelson, 2009 ;Schindler & Horner, 2005 ;Wood, Ferro, Umbreit, & Liaupsin, 2011 ). Early research provided demonstrations that the identifi cation of function and the design of interventions that were assessment-based were effective in reducing challenging behavior in young children.…”
Section: Evidence Of Effectiveness Of Ipbsmentioning
confidence: 99%